The emerging role of miR-20b in human cancer and other disorders: Pathophysiology and therapeutic implications - Khalilian, Sheyda; Abedinlou, Hamid; Hussen, Bashdar Mahmud; Imani, Seyedeh Zahra Hosseini; Ghafouri-Fard, Soudeh (Frontiers in Oncology, 2022)
miR-20b is a microRNA with diverse and somehow contradictory roles in the pathogenesis of human disorders, especially cancers. It has been known to be a tumor suppressor in colon cancer, renal cell carcinoma, prostate cancer, osteosarcoma and papillary thyroid cancer. In lung cancer and breast cancers, both tumor suppressor and oncogenic effects have been identified for this miRNA. Finally, in T cell leukemia, hepatocellular carcinoma, esophageal squamous cell carcinoma and cervical and gastric cancers, miR-20b is regarded as an oncogenic miRNA. In several types of cancer, dysregulation of miR-20b has been recognized as a predictive marker for patients' survival. Dysregulation of miR-20b has also been recognized in Alzheimer’s disease, diabetic retinopathy, myocardial ischemia/infarction, chronic hepatitis B and multiple sclerosis. In the current review, we have summarized the miR-20b targets and related cellular processes. We have also provided a review of participation of this miRNA in different human disorders.